Collaborative Governance in an Effort to Strengthen the Corporate Social Responsibility Program in the Health Field in the City of Bandung - Ade Sudrajat; Kamal Alamsyah; Thomas Bustomi (Pasundan Social Science Development, 2023)
This research aims to determine the implementation of the company's Corporate Social Responsibility (CSR) or Environmental Social Responsibility (TJSL) Program in the health sector in Bandung City, which to date has not gone according to expectations. The research method that the author uses in this research is descriptive analysis with a qualitative approach. Data collection was carried out by means of observation, in-depth interviews and documentation studies. Meanwhile, the data analysis technique used was Analytical Hierachy Process (AHP), with the aim of measuring the strength, priority and consistency of various criteria and alternatives in each dimension, namely focusing on collaborative research. Governance is determined by the Context, Driver and Collaboration Dynamics system. The results of the research state that the Corporate Social Responsibility Program in the health sector in Bandung City has been running well. To improve CSR programs more effectively, this can be done by prioritizing Collaborative Process factors which are supported by Drivers, which are also influenced by System Contex. Collaborative Dynamics factor, an important aspect to prioritize is increasing Capacity for Joint Action which is supported by Shared Motivation based on Principled Engagement, then Collaboration Dynamics itself is supported by the existence of Drivers who influence it.System Contextsin this case it influences all factors (collaboration dynamics and drivers). Referring to the findings, aspects that need to be emphasized are attention to Resource Conditions and Socio-economic/Cultural Health & Diversity. This can all be realized well with Network Connectedness, Levels of Conflict/Trust, and Political Dynamics/Power Relations that are in harmony. The appropriate model related to Collaborative Governance as an effort to strengthen the Corporate Social Responsibility program in the health sector in Bandung City is to optimize and modify the model adopted from Emerson & Nabatchi (2015b) and Ansell & Gash (2008). The results of this adoption can in turn become an initial benchmark in implementing other CSR programs or other similar programs, both in the city of Bandung and in other regions.